Dynamics of gas exchange parameters during vibroacoustic pulmonary therapy in patients with postoperative respiratory failure after prolonged abdominal surgery - A. V. Andryushchenko; V. V. Subbotin; K. V. Shadrina; E. N. Savina (Messenger of ANESTHESIOLOGY AND RESUSCITATION, 2026)
The objective was to evaluate the effect of vibroacoustic pulmonary therapy (VAPT) on the dynamics of gas exchange parameters (PaO 2 , PaCO 2 , SpO 2 , PaO2/FiO 2 ratio and respiratory rate) compared with standard percussion drainage massage (PM) in patients with early postoperative respiratory failure after prolonged abdominal surgery. Materials and methods . A single-center prospective randomized study was conducted at Loginov Moscow Clinical Scientific Center in 2023–2025. Among 2,716 patients undergoing prolonged abdominal surgery (≥ 180 min from induction of anesthesia), postoperative respiratory failure was verified in 124 patients (4.6%). After stratified randomization according to surgical approach, patients were allocated to VAPT (n = 58) and PM (n = 66) groups. Arterial blood gases were assessed before treatment and 30 min after each of three sessions. Within-group dynamics were analyzed using the Friedman test with Durbin – Conover pairwise comparisons and Bonferroni correction (p < 0.008); between-group comparisons were performed using the Mann – Whitney U test (p < 0.05). Results . Baseline SpO 2 , PaO 2 and respiratory rate were comparable between groups (p > 0.05). In the VAPT group, baseline PaO 2 /FiO 2 was lower and PaCO 2 was higher; this was considered when interpreting between-group differences. After three sessions in the VAPT group, PaO 2 increased to 86.0 [84.0–94.0] mm Hg, PaCO 2 decreased to 38.0 [36.0–39.0] mm Hg, PaO 2 /FiO 2 reached 404.0 [389.0–427.0], SpO 2 reached 97.0 [96.0–97.0]%, and respiratory rate decreased to 16.0 [16.0–17.0] per min (p < 0.001 for within-group dynamics). In the PM group, changes were less pronounced: PaO 2 reached 74.0 [72.0–90.0] mm Hg, PaCO 2 stabilized at 44.0 [41.3–45.8] mm Hg, PaO2/FiO 2 reached 343.0 [333.0–359.0], SpO 2 reached 95.0 [94.0–95.0]%, and respiratory rate was 18.0 [17.0–18.0] per min. Post-treatment between-group differences were statistically significant for all evaluated parameters. Conclusion . In patients with early postoperative respiratory failure after prolonged abdominal surgery, inclusion of VAPT in the postoperative management program was associated with more pronounced improvement in oxygenation and ventilation compared with standard percussion massage. These findings allow VAPT to be considered a promising component of early respiratory rehabilitation; further studies with predefined clinical endpoints are needed to confirm its clinical effect.